Sistem Rekomendasi Lapangan Futsal berbasis Android dengan Metode TOPSIS - Faishal Pradipta Astungkoro; Ratih Kartika Dewi; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Futsal is a sport based on soccer, played by five player per team, uses smaller ball and mainly indoors. Due to many available options for futsal pitches in Malang city has caused somewhat a problem in choosing pitches based on people's interests in renting pitches. There are five factor which affects people's interest in choosing rental pitches such as price, promotions, facilities, and contact person availability. Therefore, the solution for this problem is to develop an Android based decision support system to recommend futsal pitches. System will recommend futsal pitches with TOPSIS method based on distance, price, and amount of facilities. Recommendation results also displays detailed information such as address, facilities, price, distance, operational time, contact person, and amount of pitches. The blackbox test results of the implemented system reach 100% score which all the functionality is valid. Then, algorithm validation test result for TOPSIS implementation and manual calculation also gave the same result. And last but not least, usability test result for the system reached 80 point from five respondent. Therefore, the system has grade B with user acceptance category as acceptable, grade scale level category as B, and adjective rating category as excellent.